Digital Supervision for Critical Awareness and Ethical Technology Integration in Education: Pengawasan Digital untuk Kesadaran Kritis dan Integrasi Teknologi yang Beretika dalam Pendidikan - Fitrotul Choiriyah; Mochamad Nashrullah; Mochamad Nursalim; Amrozi Khamidi (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The digital era has transformed education, enhancing access, efficiency, and learning personalization through technology. Specific Background: In Indonesia, the COVID-19 pandemic accelerated technological adoption in education supervision, crucial for improving teaching quality despite challenges like limited infrastructure, digital literacy, and resistance to change. Knowledge Gap: Limited research addresses how digital supervision integrates critical awareness to evaluate the ethical, social, and pedagogical impacts of technology. Aims: This study explores how digital education supervision enhances teacher professionalism, critical awareness, and effective technology use in learning. Results: Digital supervision, utilizing tools like Learning Management Systems (LMS) and e-supervision platforms, enables real-time teacher monitoring, reflective dialogue, and data-driven feedback while fostering educators' ability to assess technology's pedagogical value and ethical implications. Novelty: It introduces a philosophical framework—ontology, epistemology, and axiology—to position digital supervision as both a practical tool and transformative agent, addressing gaps in digital literacy and infrastructure inclusivity. Implications: The findings advocate for comprehensive policies, digital literacy training, and collaborative strategies, ensuring supervision effectively integrates critical awareness and technology efficiency to drive sustainable, inclusive educational transformation. Highlights: Digital supervision enhances real-time monitoring, reflective dialogue, and data-driven feedback. Integrating critical awareness ensures ethical and pedagogical use of technology in education. A philosophical framework—ontology, epistemology, and axiology—supports inclusive supervision strategies. Keywords: Digital Education Supervision, Critical Awareness, Technology Effectiveness, Digital Literacy, Teacher Professionalism Development